Development of zirconia ceramic based feedstock for additive manufacturing technology - Wong, Zong Qi (2023)
Additive Manufacturing (AM) also known as 3D printing, has become a hot topic of research in recent years. It offers several advantages over traditional manufacturing methods, such as flexibility, waste reduction and dimensional accuracy. However, there is limited research research on the rheological and thermal properties of Zirconia-based feedstock with varying solid loading. Additionally, there is a lack of studies exploring the mechanical properties of sintered specimens with different chemical solvent debinding methods and ceramic solid loading. Furthermore, the extent to which mechanical properties are affected by altering printing parameters remains uncertain. In this research, the pellet feedstock will consist of zirconia doped with 3 mol% yttria as the ceramic based material. It was mixed with low-density polyethylene (LDPE), paraffin wax (PW) and stearic acid (SA) as the binders for fused deposition modelling (FDM) 3D printer. The feedstock with different solid loading percentages, which are 60 vol%, 65 vol% and 68 vol% were analysed. Additionally, the feedstocks maintained a constant ratio of LDPE:PW=40:60 and SA with a constant rate of 2.27 mg/